Endosome-based protein trafficking and Ca2+ homeostasis in the heart - Curran, Jerry; Makara, Michael A.; Mohler, Peter J. (Frontiers in Physiology, 2015)
The ability to dynamically regulate, traffic, retain, and recycle proteins within the cell membrane is fundamental to life and central to the normal function of the heart and cardiovascular system. In the heart, these systems are essential for the regulation of cardiac calcium, both at the level of the plasma membrane, but also at local domains of the endoplasmic reticulum, sarcoplasmic reticulum, mitochondria, nucleus, and nuclear envelope. One intracellular pathway often overlooked in relation to cardiovascular calcium regulation and signaling is the endosome-based trafficking pathway. Highlighting its importance, this system and its molecular components are evolutionarily conserved across all metazoans. However, remarkably little is known of how endosome-based protein trafficking and recycling functions within mammalian cells systems, especially in the heart. The vast majority of what is known has been derived from heterologous cell systems. However, recently, more appropriate cell and animal models been developed that have allowed researchers to begin to understand how this system functions within the intact physiological environment. All excitable cells, including cardiomyocytes, depend on the proper expression and organization of multiple ion channels, pumps, exchangers, and transporters within the plasma membrane. As the endosomal system acts to regulate the expression and localization of membrane proteins, understanding the in vivo function of this system in the heart is important. This review will focus on endosome-based protein trafficking in the heart in both health and disease. Special emphasis will be given to the role played by the family of endocytic regulatory proteins, C-terminal Eps15 homology domain -containing proteins (EHDs), as recent data demonstrates that this family of proteins is essential for the proper trafficking and localization and of key proteins involved in excitation-contraction coupling.